Assessing the Influence of Summer Organic Fertilization Combined with Nitrogen Inhibitor on a Short Rotation Woody Crop in Mediterranean Environment - Anita Maienza; Giovanni Mughini; Luca Salvati; Anna Benedetti; Maria Teresa Dell'Abate (International Journal of Forestry Research)
The European Union Directive 91/676/EEC, known as Nitrates Directive, has dictated basic agronomic principles regarding the use of animal manure source as well as livestock and waste waters from small food companies. The use of nitrification inhibitors together with animal effluents as organic fertilizers could be beneficial for nutrient recycling, plant productivity, and greenhouse gas emission and could offer economic advantages as alternative to conventional fertilizers especially in the Mediterranean region. The aim of the present study was to investigate differences in plant productivity between bovine effluent treatments with (or without) addition of a nitrification inhibitor (3,4 DMPP) in a short rotation woody crop system. Results of the field experiment carried out in a Mediterranean dry environment indicated that the proposed strategy could improve tree growth with indirect, beneficial effects for agroforestry systems.